2016
DOI: 10.18632/oncotarget.8623
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stromal cell-secreted lactate induces M2-macrophage differentiation by metabolic reprogramming

Abstract: Human mesenchymal stromal cells (MSC) have been shown to dampen immune response and promote tissue repair, but the underlying mechanisms are still under investigation. Herein, we demonstrate that umbilical cord-derived MSC (UC-MSC) alter the phenotype and function of monocyte-derived dendritic cells (DC) through lactate-mediated metabolic reprogramming. UC-MSC can secrete large quantities of lactate and, when present during monocyte-to-DC differentiation, induce instead the acquisition of M2-macrophage feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 73 publications
3
87
0
2
Order By: Relevance
“…We have recently shown that lactate impairs macrophage metabolic reprograming after LPS activation in a GPR81-independent manner (22), which has also been associated with blunting the proinflammatory cytokine response (46). In accordance with these results, Selleri et al (47) have shown that local increase of lactate in the environment of mesenchymal stromal cells shifts macrophage M1 activation toward the less inflammatory M2 (47). Colegio et al (48) have shown also the blunting of M1 macrophage activation in the solid tumor environment due to high lactate production of Warburg metabolism of tumor cells (48).…”
Section: Discussionsupporting
confidence: 52%
“…We have recently shown that lactate impairs macrophage metabolic reprograming after LPS activation in a GPR81-independent manner (22), which has also been associated with blunting the proinflammatory cytokine response (46). In accordance with these results, Selleri et al (47) have shown that local increase of lactate in the environment of mesenchymal stromal cells shifts macrophage M1 activation toward the less inflammatory M2 (47). Colegio et al (48) have shown also the blunting of M1 macrophage activation in the solid tumor environment due to high lactate production of Warburg metabolism of tumor cells (48).…”
Section: Discussionsupporting
confidence: 52%
“…12,13 Besides, tumor cell metabolites may also control M phenotype. Selleri and co-workers showed that lactate, secreted by mesenchymal stromal cells, skewed GM-CSF/IL-4 driven dendritic cells maturation from monocytes to M2 M s. 14 In a similar fashion, Colegio and co-workers showed that lactate can promote M2 M phenotype through hypoxia induced factor-1 (HIF-1 ) stabilization. 15 Indeed, lactate may be secreted at high concentration by tumor cells, due to their metabolic status.…”
Section: Introductionmentioning
confidence: 91%
“…An array of studies have demonstrated the capacity for MSC to modulate inflammatory M1 macrophages and promote anti-inflammatory M2 macrophages [15,37,40]. The recent progress made in the field of immunometabolism has been reflected in the MSC field, with Selleri et al [39] reporting the capacity of umbilical cord MSC (UC-MSC) to promote an M2 phenotype in a lactate-dependent manner. The M2 gene expression signature was confirmed by expression of typical macrophage and M2 gene transcripts such as CD14, CD16, CD68 and IL-10.…”
Section: Characterizing Macrophage Phenotypesmentioning
confidence: 99%